University Students’ Awareness of, Access to, and use of Artificial Intelligence for Learning in Kwara State - Alimi, Adebayo Emmanuel; Buraimoh, Oluwaseun Funmilola; Aladesusi, Gboyega Ayodeji; Babalola, Ebenezer Omolafe (Universitas Pendidikan Indonesia (UPI), 2021)
This study determined university students’ awareness of, access to, and use of artificial Intelligence for learning in Kwara State. The study adopted descriptive research of the survey type. This study adopted a descriptive research design of the survey method and employed a three-sectioned questionnaire to elicit information from the respondents. The sample size included a multistage sample of 200 undergraduates across three universities in Kwara state. Descriptive statistics and inferential statistics were employed to answer and test the formulated hypotheses at a 0.05 level of significance. The findings of the study were that majority of the university students are not aware of Artificial intelligence for learning and there was no significant difference between male and female university students’ awareness of the use of artificial intelligence for learning. This study concluded that students' ability to explore digital resources such as AI is dependent on their awareness and access to digital technologies. A lack of these will result in a lack of use and lack of skill to use them.